Before Asking “What Happens Next?”: The Compatibility Between the Olympic Education Principles and The Objectives of Sport for Development and Peace* - YILMAZ, SEMİH (My University, 2024)
The United Nations Office on Sport for Development and Peace has been closed in 2017 and its mission has been conveyed to the International Olympic Committee. The aim of this article is therefore to explore whether the principles of Olympic Education, based on Olympism and the Olympic Movement, are compatible with the objectives of Sport for Development and Peace. Qualitative research method was used in this research. And phenomenological research design was adapted as an instructive method for collecting and analyzing data. In-depth, semi-structured, face-to-face interviews were conducted with 6 participants whom were selected through purposive sampling based on their expertise on the topics of the research question. The resulting data was compiled using descriptive analysis and classified using content analysis. According to 11 main themes and 2 sub-themes that have been deducted, it has been revealed that Olympic Education principles and Sport for Development and Peace objectives complement each other in terms of conceptual basis and practice. On the basis of the research findings, the following conclusions were drawn: The participants of the Sport for Development and Peace programmes need to take active roles in the process; the policy resolutions upon the research subjects need to be implemented fully and effectively; the stakeholders in the Olympic Education and Sport for Development and Peace processes need to be all in cooperation and coordination; the sustainability of the process needs to be maintained; the strategic partnership between the United Nations and the International Olympic Committee needs to be maintained on an equal footing.
Keywords: Beden Eğitimi ve Spor; Physical Education and Sports; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION, SCIENTIFIC DISCIPLINES; Sport; Olympic education; Sport for development and peace